FORM AND MESSAGE OF ADVERTISING IN CENTRAL JAVA CORPORATE SOCIAL RESPONSIBILITY DJARUM FOUNDATION - Nugraheni, Ekky (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2019)
The purpose of this research to explain (1) how the form, structure, and theme Jelajah Jawa Tengah advertising CSR Djarum Foundation; (2) how is the message contained in the ads Jelajah Jawa Tengah CSR Djarum Foundation as works of visual communication. Data collection techniques used are observation, interview, and question form. This study used a descriptive qualitative research approach. Data collection techniques using observation, interviews and questionaires.Validation techniques using triangulation of source and triangulation techniques Technique of data analysis encompasses the reduction, withdrawal, and the presentation of the summary.The results of this research are as follows. First, shaped of Jelajah Jawa Tengah ads is video, structure of ads consists of 10 scene, the themes is a social theme. Second, there are verbal and non verbal messages in. The verbal messages conveyed through advertising want to show that in Central Java had a complete destination for sightseeing. Non verbal messages conveyed through ads browse Central Java indirectly those ads also want to exhibit a good image of the PT. To the community that PT. Djarum is very caring of the environment around. Advice that can be conveyed by the author is font type should be Arial, the duration is not too long, make the duration in 2 minutes, the selection of the actor must be younger and the ads format more completely